Comparative evaluation of sea-urchin larval stage sensitivity to ocean acidification. (October 2017) - Passarelli, M.C.; Cesar, A.; Riba, I.; DelValls, T.A.
Abstract: Changes in the marine carbonate system may affect various calcifying organisms. This study is aimed to compare the sensitivity of embryo-larval development of two species of sea urchins ( Paracentrutos lividus and Lytechinus variegatus ) collected and exposed to samples from different coastal zone (Spain and Brazil) to ocean acidification. The results showed that the larval stages are very sensitive to small changes in the seawater's pH. The larvae from P. lividus species showed to be more sensitive to acidified elutriate sediments than larvae from L. variegatus sea urchin. Furthermore, this study has demonstrated that the CO2 enrichment in aquatic ecosystems cause changes on the mobility of the metals: Zn, Cu, Fe, Al and As, which was presented different behavior among them. Although an increase on the mobility of metals was found, the results using the principal component analysis showed that the pH reduction show the highest correlations with the toxicity and is the main cause of embryo-larval development inhibition. In this comparative study it is demonstrated that both species are able to assess potential effects of the ocean acidification related to CO2 enrichment by both near future scenarios and the risk associated with CO2 leakages in the Carbon Capture and Storage (CCS) process, and the importance of comparative studies in different zones to improve the understanding of the impacts caused by ocean acidification. Highlights: CO2 -induced acidification changes the metal mobility from Brazilian and Spanish sediments. The pH reduction causes effects on embryo-larval development of sea urchins. The tropical sea urchin Lytechinus variegatus shows to be more tolerant to ocean acidification than Paracentrutos lividus . The ICpH50 for the embryo-larval development was ranged from pH 7.30 to 6.79. The As dissolved in the elutriate sediment was correlated with the pH reduction and toxicity of the sediment.